2010
DOI: 10.1017/s1481803500012549
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of capnometry versus pulse oximetry during procedural sedation and analgesia on room air

Abstract: Objective:Important questions remain regarding how best to monitor patients during procedural sedation and analgesia (PSA). Capnometry can detect hypoventilation and apnea, yet it is rarely used in emergency patients. Even the routine practice of performing preoxygenation in low-risk patients is controversial, as supplementary oxygen can delay the detection of respiratory depression by pulse oximetry. The purpose of this study was to determine whether the capnometer or the pulse oximeter would first detect res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…The clinical significance of transient hypoventilation, however, is questionable in that it denotes patients at risk of hypoxia rather than clinically important RD. [9] Although it did not occur in our study, premature diagnosis of RD may, in fact, be deleterious to patients might be unnecessarily subjected to bag valve mask ventilation, insufflating their stomachs with air, and increasing their chances of aspiration. [10] This might be especially true in the case of ultra short acting agents, where momentary apnea (safe in the presence of adequate pre-oxygenation) is likely to correct itself spontaneously as the effect of the drug wears off.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…The clinical significance of transient hypoventilation, however, is questionable in that it denotes patients at risk of hypoxia rather than clinically important RD. [9] Although it did not occur in our study, premature diagnosis of RD may, in fact, be deleterious to patients might be unnecessarily subjected to bag valve mask ventilation, insufflating their stomachs with air, and increasing their chances of aspiration. [10] This might be especially true in the case of ultra short acting agents, where momentary apnea (safe in the presence of adequate pre-oxygenation) is likely to correct itself spontaneously as the effect of the drug wears off.…”
Section: Discussionmentioning
confidence: 63%
“…Other investigators, however, have failed to show a benefi t to patients when comparing ETC with PO for detecting RD. [9,20] With regard to ETC preventing hypoxia, Deitch et al [13][14][15] found hypoxia in 25% of patients monitored by ETC, compared with 42% of those where the sedationist was blinded to the ETC reading [difference of 17% (95%CI 1.3-33)]. They also noted that all cases of hypoxia were identified by ETC before onset (100% sensitivity) although 32/132 ETC monitored patients exhibited respiratory depression without going on to hypoxia [64% specifi city (95%CI 53%-73%)].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunately, room air Pulse oximetry is quite sensitive in the detection of the onset of sedation-associated hypoventilation. It is a myth that capnometry offers any advantage over room air Pulse oximetry [5,6] . Supplemental oxygen prevents or delays oxygen desaturation resulting from hypoventilation induced by sedation.…”
Section: Administration Of Supplemental Oxygen To Increase Patient Samentioning
confidence: 99%